DESAIN DAN IMPLEMENTASI SISTEM INFORMASI RESERVASI TEMPAT PADA CAFÃ TAHU BERBASIS WEB - Kurniawan, Andre; Husni, Mochamad (DINAMIKA DOTCOM, 2013)
The process of booking a place at Café Tahu who still uses a simple method that is often inhibits the activity on the site. Resulting in an error on information received either from the Café Tahu or from the consumer. While the design of the developed system aims to provide convenience and data processing services for consumers as well as the management.From the analysis shows that the use of information systems place a web-based reservation is very helpful for the Café Tahu, and also for the customer itself in the reservation process easier place to place reservations. With applications that can be widely accessed, then this place reservation system will provide better service that is provided by Café Tahu against the customer. Key words: The Reservation Information Systems